ADDRESSING MATERNAL MORTALITY IN KANSAS: A COMPREHENSIVE ANALYSIS OF HEALTH DISPARITIES AND STATE INITIATIVES - Gregory, Anna (My University, 2024)
The way we intervene, educate, and provide maternal care has a profound impact on public health. Access to high-quality maternal healthcare and education is essential for maternal well-being. However, significant health disparities, such as disproportionately high rates of maternal mortality, continue to exist in many communities, particularly among racial and ethnic minorities. These disparities are often driven by social determinants of health, including socioeconomic status, geographic location, systemic barriers to care, and more. Despite advancements in medical knowledge and technology, many women still struggle to access comprehensive prenatal, perinatal, and postpartum care. Addressing these gaps requires a multifaceted approach that includes policy changes, community engagement, healthcare provider education, and targeted interventions to reach underserved populations. Several initiatives, such as the Fourth Trimester Initiative, the MAVIS Project, and collaborations between the Kansas Department of Health and Environment and various health committees, have been established to address the maternal mortality rate and its contributing factors in Kansas. These efforts focus on improving maternal health outcomes through enhanced screening, provider education and training, and addressing social determinants of health. This project was conducted at the Kansas Department of Health and Environment - Bureau of Family Health and involved surveying Maternal Health Innovation Task Force members. Additionally, two infographics were created for information sharing in future Maternal Health Innovation Task Force meetings and the future published (2016-2022) Kansas Maternal Mortality Review Committee report. These projects focused on education, advocacy, and decision-making efforts to improve maternal health outcomes in Kansas.
Keywords: Maternal mortality; Health disparities; Maternal health initiatives; Pregnancy-associated deaths; Pregnancy-related deaths; Maternal mortality Kansas